Education as development : deprivation, poverty, dispossession - Rupavath, Ramdas (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book is an in-depth analysis of the educational development of tribals in India. Education as Development: Deprivation, Poverty, Dispossession is a significant new addition for understanding educational and economic setbacks experienced by the marginalized in India. The volume: Focuses on how the social, economic and education systems have evolved over time in India and identifies the scope of development in these areas; Provides a rational structure for readers to understand how the Adivasi in India can be made to fit in the modern designed education system; Highlights the problems of the marginalized - such as income inequality, education, health, housing, governance, civil society environment and infrastructure and others which hampers their overall growth. This book will be of great interest to students and researchers and policy makers in the fields of education, minority studies, indigenous studies, sociology of education, and South Asian studies"--
Educating the tribal population in the era of globalization : the supply and demand driven approaches / Subir Maitra -- Tribal life in schools : critical pedagogy / Ramdas Rupavath -- Educational status of women and girl child : Lambadi tribe in Telangana State / M.Ramulu -- Education and emancipation of tribal children : analysing human development in lens of capability approach perspective / Vikram Singh -- Interactions : micro politics, quality, and educational interventions / Pradeep Ramavath J -- Inclusion of the excluded : a probe into the status of the tribal women in West Bengal / Gouri Sankar Nag and Kaushik Mukherjee -- Is education challenging task for particularly tribal venerable groups in 21st century? : with reference of Adilabad, Telangana / Sidam Madhukar -- Problems of tribal education in India : an analysis / Dipak Kumar Dash -- Tribal education : dimensions of communities in India / Ramdas Rupavath -- Development-induced displacement and resettlement of indigenous communities in India : policy and practice / Ram Babu Mallavarpu -- Marginalized communities in the era of globalization and North East India / K Vidya Sagar Reddy -- The nomadic tribe in India : understanding their struggle and politics of exclusion / Dattatary Bhandalkar -- The education question from the perspectives of missionaries / Ramdas Rupavath -- Socio-political awakening in Jammu and Kashmir / Nasir Ahmad Ganaie -- Tribes in India : public policy perspective / Satyam Sunkari -- Development projects and issues of displacement of tribal people in Andhra Pradesh / K. Anil Kumar.
Keywords: People with social disabilities -- Education -- India; Education -- Social aspects -- India; Ashram schools; Education and state -- India; India -- Scheduled tribes -- Education; EDUCATION / General; EDUCATION / Educational Policy & Reform / General; EDUCATION / Philosophy & Social Aspects